The Influence of Office Facilities on Employee Performance - Nasrullah, Muh.; Alan, Nur; Akib, Haedar (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
Employee performance is a set of work results or achievements that are carried out in quality and quantity by a person or group of people. One of the factors that affect employee performance is the office facility factor. This study aims to find out the description of office facilities and the description of employee performance as well as to find out the picture of the influence of office facilities on employee performance at the Lempang Village Office, Tanete Riaja District, Barru Regency. This study uses a quantitative method with the population in this study, namely all office employees, both civil servants and contract employees, totaling 31 people. Data collection was carried out by observation, questionnaire, interview and documentation techniques. The data analysis techniques in this study use descriptive statistical analysis and inferential statistical analysis. The results of this study show that office facilities are classified as good categories. Employee performance is classified as good. The results of hypothesis testing show that there is a significant influence between office facilities on employee performance at the Lempang Village Office, Tanete Riaja District, Barru Regency.